Smart societies, infrastructure, technologies and applications : first International Conference, SCITA 2017, Jeddah, Saudi Arabia, November 27-29, 2017, Proceedings /: first International Conference, SCITA 2017, Jeddah, Saudi Arabia, November 27-29, 2017, Proceedings. (2018) - Unknown
No abstract available